2005
DOI: 10.1128/jvi.79.12.7852-7859.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Suppress In Vitro Proliferation of Virus-Specific CD8+T Cells during Persistent Hepatitis C Virus Infection

Abstract: The basis of chronic infection following exposure to hepatitis C virus (HCV) infection is unexplained. One factor may be the low frequency and immature phenotype of virus-specific CD8 ؉ T cells. The role of CD4 ؉ CD25 ؉ T regulatory (T reg ) cells in priming and expanding virus-specific CD8 ؉ T cells was investigated. Twenty HLA-A2-positive patients with persistent HCV infection and 46 healthy controls were studied. Virusspecific CD8؉ T-cell proliferation and gamma interferon (IFN-␥) frequency were analyzed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
224
4
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(253 citation statements)
references
References 44 publications
17
224
4
8
Order By: Relevance
“…However, the fact that HPV infection is necessary for the development of CIN3 and cervical carcinoma should be taken into account since various viruses have been shown to drive Treg expansion. [37][38][39][40] Indeed, we found a strong association between persistent HPV infection and increased Treg frequencies. Since most persistence patients had already a persistent infection at the time of Treg testing, it remains unclear whether the persistent HPV16 infection is responsible for the increased Treg frequency or whether increased Treg frequencies predispose to persistence.…”
Section: Discussionmentioning
confidence: 72%
“…However, the fact that HPV infection is necessary for the development of CIN3 and cervical carcinoma should be taken into account since various viruses have been shown to drive Treg expansion. [37][38][39][40] Indeed, we found a strong association between persistent HPV infection and increased Treg frequencies. Since most persistence patients had already a persistent infection at the time of Treg testing, it remains unclear whether the persistent HPV16 infection is responsible for the increased Treg frequency or whether increased Treg frequencies predispose to persistence.…”
Section: Discussionmentioning
confidence: 72%
“…7 Tregs isolated from HCV-infected patients are immunosuppressive and can inactivate both HCV-specific and bystander CD4 1 and CD8 1 T cells. 8,9 Here, we show that the concentration 1 of HCVc in the blood of HCV-infected patients directly correlates with the frequency of Tregs. Furthermore, HCVc directly caused proliferation of Tregs and caused them to secrete immunosuppressive cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…The role of regulatory cells in HCV viral persistence was first studied by McDonald et al (38), who showed that T cell clones with suppressive function (IL-10-producing Trl cells) were readily isolated from patients with chronic infection, but not from those in whom the infection was controlled. Other investigators have shown that patients with persistent infections had an elevated frequency of CD4ϩCD25 high and CD25 high FoxP3ϩ T cells (39) and that ex vivo, these Treg cells could suppress the activity of HCV-specific CD8ϩ T cells (39)(40)(41)(42), suggesting that Treg cells may influence the outcome of infection. With regard to the frequency of Treg cells in patients with chronic HCV infection without MC as compared with healthy controls, we found an opposite, weak, trend; however, since this study was not constructed to answer this question, it remains to be resolved by larger ongoing studies.…”
mentioning
confidence: 99%